A hub and spokes approach to building community capacity for eating disorders in rural Western Australia. (6th February 2013) - McCormack, Julie; Watson, Hunna J.; Harris, Chris; Potts, Julie; Forbes, David
Abstract Objective To determine whether an outreach community‐based training program on eating disorders enhances perceived capacity of rural health and education professionals to respond to and manage eating disorders. Design Survey conducted upon completion of outreach training. Setting Rural Western Australia. Participants Health and education professionals working in rural Western Australia. Main outcome measures Questionnaire responses analysed via descriptive statistics and inferential tests. Results There was a significant increase in perceived ability to identify, support and/or treat people with eating disorders among health and education professionals. Conclusions Outreach training up‐skilled rural gatekeepers and introduced systemic health system benefits of increased consultation and liaison, a fine‐tuning of referral processes, a reduction in hospital admissions and better uptake of local services by patients discharged from hospital.